Hypoplastic internal carotid artery, renal artery stenosis, vertebral fusion anomaly: rare association-a case report - Kulkarni, Venu; Kariyappa, Mallesh; H., Anil Kumar; ., Gangadaraiah (International Journal of Contemporary Pediatrics, 2019)
Hypoplastic internal carotid artery has been reported in about 100 patients, most being incidentally diagnosed. Association with other anomalies rarely described. Authors report 6-year-old male presenting failure to gain weight and precordial bulge from past 6 months, past history was significant-diagnosed to have right dysplastic kidney at 8 months age. Detailed investigations revealed left hypoplastic internal carotid artery, vertebral segment anamoly, right dysplastic kidney due to right renal artery stenosis. Child was treated medically and was clinically better at latest follow up. All cases with dysplastic kidney need to be searched for vertebral and carotid anomalies, left ventricular dysfunction.